The Concept of Inherent Power in International Arbitration - Ahmet Dülger; Emre Esen (Public and Private International Law Bulletin)
The first condition to meet for arbitration proceedings to occur is the existence of an arbitration agreement between the parties to the dispute. An arbitration agreement is a pre-condition needing to be met before parties can bring their dispute before an arbitral tribunal. In addition, the arbitrators are vested with the jurisdiction of conducting the proceedings and taking decisions using the arbitration agreement. Arbitration laws, institutional arbitration rules, and international agreements may also contain provisions with regard to the arbitrators’ jurisdiction. While some powers may possibly be able to be explicitly granted to the arbitrators, the arbitrators may also be implicitly deduced as having certain inherent powers based on the aforementioned regulations. The decisions arbitrators make within the framework of inherent powers must comply with the conditions and limitations of this power. The will of the parties or the rules of law applied to the merits and procedures as well as the limitations imposed on the arbitrators will determine the boundaries of inherent powers. The discussion on what kind of decisions can be made in these cases where no prohibition is found regarding the arbitral tribunal still continues in current judicial decisions and legal academia. This article seeks the answer to the question regarding the issues and foundations upon which arbitrators can make decisions based on their inherent powers in international arbitration. The existence of a valid and enforceable arbitral award depends on whether these decisions have been made in compliance with these sources and limitations. This article aims to draw the conceptual framework of arbitrators’ inherent powers and explain the sources for these.